A deconstructive approach to the concept of power in Ini Kalilah (2018) and One Two Jaga (2018) - Nor Ain Matnoh; Zairul Anuar Md. Dawam; Sim, Chee Cheang (Human Resource Management Academic Research Society (HRMARS), 2019)
This paper analyzes the concept of power in two Malaysian films entitled Rise Ini Kalilah (2018) and Crossroads: One Two Jaga (2018) through a deconstructive postmodern approach. This concept of power is discussed through narrative elements and structures using Michel Foucault’s (1970) deconstruction approach. According to Foucault (Power, 2011) “knowledge is power” which leads to the analysis of both films aspects of power and knowledge related to national interests and social classes as well as how power affects the lives of Malaysian society. The abuse of power resulting in social and political issues such as corruption, illegal immigrant issues and educational interests are analyzed through its narrative elements such as the films’ point of view of characters. Via the analyses on particular scenes in both films, this paper aims to expose the different concept of power that is depicted in both films as the beginning of social and political unrest in Malaysia as conceived by the directors and script-writers of the movies.